Recognition of the Effect of Indirect Revascularization for Moyamoya Disease: The Balance Between the Stage Progression and Neoangiogenesis - Bao, Xiang-Yang; Wang, Qian-Nan; Wang, Xiao-Peng; Yang, Ri-Miao; Zou, Zheng-Xing; Zhang, Qian; Li, De-Sheng; Duan, Lian (Frontiers in Neurology, 2022)
Objective To explore the long-term progression of neoangiogenesis after indirect revascularization for moyamoya disease (MMD). Methods We enrolled patients who were diagnosed with MMD and treated by encephaloduroarteriosynangiosis (EDAS) surgery at our center from December 2002 through September 2009. A comparative study between short-term (6–12 months) and long-term (duration ≥ 8 years) follow-up angiographies was performed. The development of collateral circulation through EDAS was graded according to the system described by Matsushima grade system. Results A total of 78 patients who received indirect EDAS were enrolled in the study. The mean age at the first operation was 26.9 ± 15.0 years. Matsushima grades of the same hemisphere were higher at the long-term follow-up compared to the short-term follow-up. Importantly, no attenuation was observed in any hemisphere during the long-term follow-up. Fifty-one hemispheres (32.7%) and 26 hemispheres (16.6%) had progression during the short-term and the long-term follow-up respectively. The ipsilateral Suzuki stage showed a significant negative correlation with progression pace. Furthermore, higher Suzuki stages were significantly correlated with postsurgical Matsushima grade at both time points. A total of 9 strokes (11.5%) occurred in 78 patients was reported at the long-term follow-up. The annual incidence rate of recurrent strokes was higher for the stage progression group than for the stable group. Conclusions For MMD patients, postsurgical neoangiogenesis after indirect bypass continuously improved with time. The short-term progression of the Internal carotid artery (ICA) might be attributed to cerebral revascularization, while the long-term progression should be attributed to natural progression of disease.